PENGARUH KEBIJAKAN PERUBAHAN KURIKULUM TERHADAP PEMBELAJARAN DI SEKOLAH - Ratih Setyorini; Martono Martono; Agung Hartoyo (STKIP Persada Khatulistiwa Sintang, 2023)
The internal curriculum is a very important aspect for the success and progress of education. Curriculum changes are based on the awareness that developments and changes that occur in social, national and state life in Indonesia cannot be separated from the influence of global changes, developments in science and technology as well as arts and culture. Apart from that, the educational curriculum reform that has been carried out. Judging from the 1975, 1984, 1994, 2004 (KBK), 2006 (KTSP), and 2013 curricula, it has not had a positive impact on the development of quality in the world of education, so that up to now the quality of our education still low. The role of curriculum developers is very important for the world of education to achieve better learning processes and outcomes. This article wants to describe in more detail what curriculum policies are, curriculum changes, problems with curriculum changes, the impact of curriculum changes on learning in schools.